The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fpsyg.2021.750711
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Digital Game-Based Learning on Learning Motivation and Performance Under Social Cognitive Theory and Entrepreneurial Thinking

Abstract: This study aims to investigate the effects of students’ learning motivation and learning performance in a digital game-based learning setting and the structure of competition. This study uses Social Cognitive Theory, which emphasizes the bidirectional effects between personal factors, environmental factors, and behavior. We use the emotional state as the personal factor, social support as the environmental factor, learning performance as behavior. We also use self-efficacy and learning motivation as the mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 74 publications
2
12
0
2
Order By: Relevance
“…This study confirmed some implication from other studies, which has indicated that the game-based learning method has a positive effect on declarative knowledge delivery (Clark et al. , 2016; Chen and Huang, 2013) and learners' motivation enhancement (Chen Tu, 2021; Ozcelik et al ., 2013; de Freitas S 2006). In addition, the findings argued that the learners enjoy lower-skill level games instead of higher-skill level games mentioned in a previous study (Liu et al ., 2013).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This study confirmed some implication from other studies, which has indicated that the game-based learning method has a positive effect on declarative knowledge delivery (Clark et al. , 2016; Chen and Huang, 2013) and learners' motivation enhancement (Chen Tu, 2021; Ozcelik et al ., 2013; de Freitas S 2006). In addition, the findings argued that the learners enjoy lower-skill level games instead of higher-skill level games mentioned in a previous study (Liu et al ., 2013).…”
Section: Discussionsupporting
confidence: 90%
“…According to the results of the pre-test and post-test, the research team sees the potential of using advergames to improve children's learning experience and outcomes by drawing them into the process, which is supported by prior similar research in using digital games for learning (Girard et al, 2013;Klopfer et al, 2012). This study confirmed some implication from other studies, which has indicated that the game-based learning method has a positive effect on declarative knowledge delivery (Clark et al, 2016;Chen and Huang, 2013) and learners' motivation enhancement (Chen Tu, 2021;Ozcelik et al, 2013;de Freitas S 2006). In addition, the findings argued that the learners enjoy lower-skill level games instead of higher-skill level games mentioned in a previous study (Liu et al, 2013).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Motivation is the direct cause of student learning; motivation directly causes or sustains student learning behavior [18]. University students' learning motivations are affected by personal cognition.…”
Section: Learning Motivation Researchmentioning
confidence: 99%
“…Considerados educativos e divertidos, os jogos sérios são altamente agradáveis, atraentes e intrinsecamente motivadores 96,97 . Diferem de jogos de entretenimento em seu objetivo de educar e promover a mudança de comportamento 98 .…”
Section: Jogos Eletrônicosunclassified